Agreement of macular oedema features between FFA And HRT II and evaluation of visual function, macular oedema index and quality of life post laser photocoagulation in diabetic macular oedema - Embong, Zunaina (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Objectives: To evaluate the agreement of macular edema features between FFA and HRT, and also to evaluate the visual function, macular edema index and quality of life between pre and post laser photocoagulation in diabetic macular edema. Methodology: Sixty-seven patients were subjected to HRT, FFA (served as the gold standard) and laser photocoagulation. The visual function, macular edema index and quality of life measurements were done at baseline and three months post laser photocoagulation. Results: Topographic edema map of HRT has better sensitivity and specificity compare with other modules. There is a good agreement between topographic edema map and macular edema index (MEI) thickness map. There were improvement in visual function, macular edema index, and quality of life at 3 months post laser photocogulation. Conclusion: Topographic edema map of HRT has better sensitivity compared with other modules. Good agreement exists between topographic edema map and MEI thickness map. The visual function, macular edema index and quality of life were improved post laser photocoagulation.